2016
DOI: 10.1371/journal.pone.0165516
|View full text |Cite
|
Sign up to set email alerts
|

ZHX1 Promotes the Proliferation, Migration and Invasion of Cholangiocarcinoma Cells

Abstract: Zinc-fingers and homeoboxes 1 (ZHX1) is a transcription repressor that has been associated with the progressions of hepatocellular carcinoma, gastric cancer, and breast cancer. However, the functional roles of ZHX1 in cholangiocarcinoma (CCA) have not been determined. We investigated the expression and roles of ZHX1 during the proliferation, migration, and invasion of CCA cells. In silico analysis and immunohistochemical studies showed amplification and overexpression of ZHX1 in CCA tissues. Furthermore, ZHX1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…ZHX1, the first identified factor of this family, has been proposed as a tumor suppressor in many cancer types 29–33. However, two recent studies suggested that ZHX1 may serve as an oncogene in glioblastoma and cholangiocarci- noma 34,35. Upregulated ZHX1 expression in tumor specimens compared with that in normal tissues has been found to be correlated with reduced survival of cancer patients 34,35.…”
Section: Discussionmentioning
confidence: 99%
“…ZHX1, the first identified factor of this family, has been proposed as a tumor suppressor in many cancer types 29–33. However, two recent studies suggested that ZHX1 may serve as an oncogene in glioblastoma and cholangiocarci- noma 34,35. Upregulated ZHX1 expression in tumor specimens compared with that in normal tissues has been found to be correlated with reduced survival of cancer patients 34,35.…”
Section: Discussionmentioning
confidence: 99%
“…For the Zinc fingers C2H2-type|PR/SET domain family, one of its members, ZHX1 , was regulated by a cluster of five enhancers in 22 samples, which covered 12% of 184 tumor sample with detected super-enhancer regulation. As a transcription repressor, ZHX1 has been associated with the progressions of cholangiocarcinoma, hepatocellular carcinoma, gastric cancer, and breast cancer [ 18 ]. For Pleckstrin homology domain containing genes, there are two AKT proteins ( AKT1/2 ), which regulate cell proliferation and growth.…”
Section: Resultsmentioning
confidence: 99%
“…39 However, in cholangiocarcinoma, hepatocellular carcinoma and cervical cancer, ZHX1 promotes cancer progression. [40][41][42] In glioma, ZHX1…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, ZHX1 impedes the proliferation and migration of cancer cells by inducing cell cycle arrest and apoptosis 39 . However, in cholangiocarcinoma, hepatocellular carcinoma and cervical cancer, ZHX1 promotes cancer progression 40–42 . In glioma, ZHX1 is also shown to be an oncogene, and its high expression can facilitate TWIST1 and SNAI2 expression, comprising crucial modulators in epithelial–mesenchymal transition 22 .…”
Section: Discussionmentioning
confidence: 99%